Modest Fashion: Overview Of Consumer Intention Based On Product Quality, Design, And Lifestyle With Islamic Branding As A Moderating Variable - Hana, Kharis Fadlullah; Sari, Sisca Apriliana; Rahmawaty, Anita (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
The growth of the Indonesian Muslim fashion industry, which is in the second position, has triggered the government to make Indonesia the center of world Muslim fashion. However, some industries do not know much about the factors that can increase interest in modest fashion. The purpose of this study was to examine the factors that influence the purchase intention of modest fashion by being moderated by Islamic branding. The variables tested are Product Quality, Design and Lifestyle. This research method uses quantitative methods with post positivism paradigm. The data was obtained using purposive sampling technique with 384 respondents from the millennial generation. The measurement scale used is a Likert scale with a value of 1-5 for a score of strongly disagree and strongly agree. Analysis of the data using the SPSS version 23. The results show that all variables affect the purchase intention of modest fashion. Testing the variables using two models, testing the direct influence between the independent and dependent variables and testing the interaction or Moderated Regression Analysis. However, if you include Islamic branding as a moderating variable, there is a variable that shows a stronger influence than others, namely product quality. Brands that have Islamic names are the highest choice of respondents. They are interested in buying modest fashion products because they are of good quality with average 3,5885 and t table which is 15.927. Recommendations from this study need to create an Islamic brand name for modest fashion products.